REFLEXIONES SOBRE WALTER BENJAMIN: APROXIMACIÓN A LA EXPERIENCIA PARA ABORDAR OTRAS FORMAS DE CONOCIMIENTO - González Morera, Héctor (2023)
This article makes emphasis on the actuality of Walter Benjamin’s thought and theories vis-à-vis cultural studies. The author discusses critically some aspects of his writings in which Benjamin articulated a new Philosophy of knowledge: Aesthetic and religious experience, art criticism and the role of the intellectual.